The effect of various designs of six-curved blade impellers on reaction rate analysis in liquid–liquid mixing vessel - Afshar Ghotli, R.; Abdul Raman, Abdul Aziz; Ibrahim, Shaliza (Elsevier, 2016)
The mixing efficiencies of impellers vary according to their designs. In this work, the effects of 6-curved-blade impellers of different curvature angles and central disk sizes on the reaction in a stirred vessel were investigated and the results were compared to that of a Rushton turbine. The impeller efficiency was defined by the ratio of reaction rate to power consumption, (rA/P). The experiments were performed at the rotational speeds of 5, 6 and 7 rps. The interaction among the experimental parameters was investigated using Response Surface Methodology. The rA/P values were found to decrease with increasing curvature angles. The lowest rA/P value was obtained for the impeller with curvature angle of 140°. The result showed that the results for Rushton turbine was relatively low compared to curved-blade impellers and increase in central disk size did not significantly affect rA/P. In conclusion, curved-blade impellers were more economically efficient than Rushton turbine.